The mechanism of the accusmatic voice and intertextuality in poetry - Yufra, Juan Wilfredo (2024)
This article will address the concept of the «accusmatic voice» in the production of meaning in poems and intertextuality as a rewriting device. Relevance is given to a reflexive purpose of these topics that are permanent marks in the western lyric tradition and especially in the contemporary poetic register.